Reconciliation policies and the effects of motherhood on employment, earnings, and poverty - Joya Misra; Michelle J. Budig; Stephanie Moller (Luxembourg Income Study (LIS), 2006)
In this paper, we examine the consequences of different welfare state strategies. We argue that four major strategies have appeared: 1) the primary caregiver/secondary earner strategy, focused on valuing the care in which women engage; 2) the primary earner/secondary caregiver strategy, focused on encouraging women's labor market participation; 3) the choice strategy, which provides support for women's employment, but also gives women the choice of emphasizing caretaking when children are very young; and 4) the earner-carer strategy, focused on helping men and women balance care and work through support for care both inside and outside of the home. We examine differences between women who are mothers of children and other women on three outcomes labor force participation rates, wage rates, and poverty rates, analyzing the effects of motherhood and marital status on labor force participation rates, annual earnings, and poverty rates. After analyzing these differences, our study suggests that the strategy taken by the earner-carer strategy is most effective at increasing equity for the widest array of women.
Keywords: 330; Sozialstaat; Familienpolitik; Sozialpolitik; Mütter; Weibliche Arbeitskräfte; Armut